β-cryptoxanthin suppresses oxidative stress via activation of the Nrf2/HO-1 signaling pathway in diabetic kidney disease - Ke, Jingjing; Zang, Hualong; Liu, Yang; Teng, Qiuping; Hua, Jiao; Peng, Dan; Wang, Ping (Frontiers in Pharmacology, 2024)
Abstract Objectives: This study aims to explore the role and investigate mechanisms of β-Cryptoxanthin (BCX) in high glucose (HG)-induced podocyte injury and renal dysfunction. Methods: In this study, db/db mice were orally treated with BCX. Blood glucose, body weight, urinary albumin creatinine ratio (ACR) was recorded to evaluate the mice renal function. The H&E, PAS staining, and transmission electron microscopy (TEM) were utilized to examine the effect of BCX on the morphological changes of glomeruli in db/db mice. In addition, reactive oxygen species (ROS) content, mitochondrial membrane potential (MMP) level, ATP level, and SA-β-gal staining were used to assess the podocyte oxidative damage, mitochondrial dysfunction and senescence. Furthermore, the effects of BCX on Nrf2/HO-1 signaling pathway were evaluated in vivo and in vitro through Western blotting, immunohistochemistry and immunofluorescence analysis. Results: In vivo, BCX reversed glomerular mesangial matrix expansion and reduced proteinuria in db/db mice, as well as decreased glomerular oxidative stress and kidney aging. Similarly, in vitro study showed that BCX effectively alleviated the oxidative stress, mitochondrial dysfunction, and senescence induced by HG in podocytes. Furthermore, we identified that the antioxidative effects of BCX are associated with the activation of Nrf2/HO-1 signaling pathway, and that Nrf2 knockdown partially abrogated the protective effects of BCX in vitro. Conclusions: Our study demonstrated for the first time that BCX alleviates podocyte injury in DKD by promoting Nrf2/HO-1 signaling pathways. BCX may be a potential candidate compound for preventing Diabetic kidney disease (DKD).